A comprehensive study on the avalanche breakdown robustness of silicon carbide power MOSFETs - Fayyaz, Asad; Romano, Gianpaolo; Urresti, Jesus; Riccio, Michele; Castellazzi, Alberto; Irace, Andrea; Wright, Nick (MDPI, 2017)
This paper presents an in-depth investigation into the avalanche breakdown robustness of commercial state-of-the-art silicon carbide (SiC) power MOSFETs comprising of functional as well as structural characterization and the corresponding underlying physical mechanisms responsible for device failure. One aspect of robustness for power MOSFETs is determined by its ability to withstand energy during avalanche breakdown. Avalanche energy (EAV) is an important figure of merit for all applications requiring load dumping and/or to benefit from snubber-less converter design. 2D TCAD electro-thermal simulations were performed to get important insight into the failure mechanism of SiC power MOSFETs during avalanche breakdown